An Analysis of The Effect of Macroeconomic Variables on the Profitability of Sharia Commercial Banks in Indonesia, with GDP as an Intervening Variable (2010–2024) - Rahmadani Aidil Fitrohcahya; Barianto Nurasri Sudarmawan (Master of Management, School of Business and Management, Petra Christian University, 2026)
This research is motivated by the profitability dynamics of Sharia Commercial Banks (BUS) in Indonesia, which have increased despite a slowdown in asset growth and changes in macroeconomic conditions. The study aimed to analyze the effects of Foreign Direct Investment (FDI), money supply, and exchange rates on ICB profitability, with Gross Domestic Product (GDP) serving as an intervening variable. The method used is a quantitative approach, employing time-series data from 2010 to 2024 and analyzing it using path analysis via stepwise regression. The results indicate that the influence of macroeconomic variables on profitability is not entirely direct but operates indirectly through GDP. FDI and the exchange rate have significantly affected profitability, both directly and indirectly, whereas the money supply has not. These findings confirm that GDP is the primary transmission channel linking macroeconomic variables and Islamic banking profitability. Implicitly, this study suggests that Islamic banking performance is highly dependent on real-sector dynamics and macroeconomic stability.